Las novelas de la memoria sobre el conflicto armado en Perú desde una perspectiva de género (2021)
In 1980 an internal armed conflict began between the Peruvian Communist Party Sendero Luminoso (PCP-SL) and the armed forces of the Peruvian State. This article focuses on the function of the literary discourse during the post-conflict and more specifically on the literary strategies for the representation of violence, on the relationship between literary production, as an elite cultural production, and the subaltern groups affected during and after the conflict. It is from this angle that the novels La voluntad del molle (The Will of the Molle) (2006), by Karina Pacheco, and La sangre de la aurora (Blood of the Dawn) (2013), by Claudia Salazar, are analyzed. In these two fictions, their female characters explore different roles that make us rethink the categories of “victim” and “guilty” in the logic of the memory of the defeated. These novels cross two frontiers: the frontier of the enclosed nation and the one that separates the “victims” from the “guilty”.